RFID Technology Based Attendance Management System (International Journal of Engineering and Computer Science, 2017)
Attendance plays a vital role in evaluating a student. The traditional method of taking attendance manually is very time consuming and often leads to human error. Also there are many challenges that are faced while one adopts a manual method of taking attendance such as, difficulty in keeping the attendance list over a long period of time, lecturers forgetting the attendance register in the classroom, students illegally marking the attendance of their friends while the roll number is being called out and many more. This paper elaborates the implementation of Radio Frequency Identification based Student Attendance Management System using Open Source Software in a multi-user environment. This would eradicate the deficiencies associated with the manual attendance system since an automated approach is being adopted